2022
DOI: 10.1002/ejp.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of analgesic techniques on early quality of recovery after prostatectomy: A 3‐arm, randomized trial

Abstract: Background Prostatectomy is associated with relevant acute postoperative pain. Optimal analgesic techniques to minimize pain and enhance recovery are still under investigation. We aimed to compare the effect of three different analgesic techniques on quality of recovery. Methods This investigator‐initiated, prospective, randomized, three‐arm, parallel‐group, active‐controlled, interventional superiority trial was performed in a Swiss teaching hospital from 2018 to 2021. Consecutive patients undergoing open or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There is no literature regarding ORP and QoR-40. A recent work by Beilstein et al [ 28 ] evaluated analgesia after radical prostatectomy with QoR-15. They evaluated the effect of three different analgesic concepts: spinal single shot, TAP block, and the systemic administration of lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…There is no literature regarding ORP and QoR-40. A recent work by Beilstein et al [ 28 ] evaluated analgesia after radical prostatectomy with QoR-15. They evaluated the effect of three different analgesic concepts: spinal single shot, TAP block, and the systemic administration of lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, We would like to thank Dr. Jjang et al for raising these questions regarding our recently published work and would like to provide clarification (Beilstein et al, 2022).…”
Section: E T T E R T O T H E E D I T O R Authors' Reply To the Commen...mentioning
confidence: 98%
“…First question (primary endpoint): Assuming that baseline QoR-15 values in all groups are comparable (which in fact was the case, see table 2 of the original article), it is from minor relevance if one compares absolute values or differences to baseline (Beilstein et al, 2022). In fact, the latter has the advantage of eliminating variation in baseline values.…”
Section: E T T E R T O T H E E D I T O R Authors' Reply To the Commen...mentioning
confidence: 99%
“…In an investigator-initiated, prospective, randomized, threearm, parallel-group, active-controlled, interventional superiority trial that included 133 patients undergoing open or robotic-assisted radical prostatectomy, Beilstein et al (2022) compared the effects of adding spinal anaesthesia, transversus abdominis plane block and intravenous lidocaine to general anaesthesia on quality of early post-operative recovery assessed by the quality of recovery-15 (QoR-15) score. They showed that the addition of three different analgesic techniques to general anaesthesia did not improve the quality of early post-operative recovery.…”
Section: Comment On 'Impact Of Analgesic Techniques On Early Quality ...mentioning
confidence: 99%